KONDISI PENGEMIS DALAM PERSPEKTIF SOSIOLOGI PENDIDIKAN DI NUSA INDAH III, PONTIANAK KOTA - Rindi Wulan Suci; Rustiyarso Rustiyarso; Izhar Salim (Universitas Tanjungpura, 2018)
Abstrack The purposes of this study were to find out the reason of school –aged beggars in doing begging activities, the way they did begging, and their daily activities for they were not going to school as they should. This research used descriptive method in the form of qualitative research. The subject of this research were school-aged beggars who did begging activities in nusa indah III, Pontianak City. Tools of data collection in this research were observation guides, interview, and documentation studies. The results of this study showed that (1) the main reason of school-aged beggars doing begging activities was to earn money, so they could help their parents to fulfill the family’s needs. (2) School-aged beggars used techniques of pity in order to take advantages of people’s compassion so they were willing to give them money. (3) It was alsoproved that school-aged beggars, who did begging activities every day without any other activities, tend to have negative mindset.Keywords : school-aged beggars, educatinal sosiology perspective